Optimization of Management of BUMDes: The Case in East Java Province - Muhammad Ridwan Basalamah; M. Cholid Mawardi (Universitas Padjadjaran, 2021)
This study aimed to describe the use of village assets in increasing the village's original income through BUMDes in Ketapanrame Village, Trawas District, Mojokerto Regency, East Java Province. This research type is qualitative research using a three-stage approach, namely the first stage with a community-based research approach. Second Stage In-depth Interview. The third stage of the Focus Group Discussion approach. The study results indicate that the management of Village-Owned Enterprises located in Ketapanrame Village, Mojokerto Regency, East Java Province, follows existing village regulations starting from the underlying legal basis, the articles of association and bylaws compiled, as well as the organizational structure. BUMDes in Ketapanrame village, East Java province, have been well managed, so that to date, they have five business units, namely, Drinking Water Management Unit, Environmental Hygiene Unit, Land and Cage Management Unit, Tourism Unit and Savings and Loans Business Unit and Partnership.